Fibrin Quantification on Bio-Scaffold Valve Explant as a Measure of Their Integration. (9th April 2021) - Agarwal, Aarushi; Gonzalez, Brittany A.; Gonzalez Perez, Marcos; Scholl, Frank; Bibevski, Steven; Ladich, Elena; Rivas Rivas Wagner, Krishna; Bibevski, Jennifer; Hernandez, Lazaro; Morales, Pablo; Lopez, Jesus; Ramaswamy, Sharan
Abstract : Objective : Critical congenital heart valve disease at birth has limited treatment options and can benefit from valves with regenerative capacities. Following a pilot study of porcine small intestinal submucosa (PSIS) bio scaffold mitral valves implanted in a juvenile baboon model, the explanted valves were subsequently quantified for fibrin content or lack thereof, as a measure of valve integration with the host. Methods : PSIS mitral valves were explanted at 3, 11 and 20 month and histologically stained (Movat's; Alizée Pathology, Inc., Thurmont, MD) and sectioned. Histological images were individually analyzed (ImageJ, NIH, Bethesda, MD), where all images were normalized with respect to the baboon native mitral valve. Following thresholding, the percentage of fibrin area (bright red regions) was computed. Results : Conclusions : Fibrin did not decrease progressively over time. Sustained presence of fibrin at 20-months post-implantation suggests that complete PSIS mitral valve integration was not achieved. This provides motivation for additional scaffold processing (e.g. with stem cells) prior to implantation, to accelerate valve tissue integration with the host.